ChemInform Abstract: Practical Method for the Cu‐Mediated Trifluoromethylation of Arylboronic Acids with CF3 Radicals Derived from NaSO2CF3 and tert‐Butyl Hydroperoxide (TBHP). Issue 8 (1st March 2013) - Ye, Yingda; Kuenzi, Stefan A.; Sanford, Melanie S.
Abstract Various important (hetero)aromatic structural motifs are available under mild conditions.